KONSTRUKSI HUKUM PEMBIAYAAN MURABAHAH DAN WAKALAH DALAM SATU TRANSAKSI PADA BANK BTPN SYARIAH; TELAAH FATWA DSN-MUI NOMOR 04/DSN-MUI/IV/2000 - Wahyudi, Anjar K, (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2019)
The purpose of this study is to find out how the construction of the DSN-MUI fatwa on murabaha financing and time in one transaction at PT Bank BTPN Syariah. This research is a qualitative research with a normative juridical approach that uses the Statue Approach method and the Case Approach method. The technique of analyzing legal materials in this study uses descriptive analysis techniques. Murabaha contract accompanied by wakalah contract at PT Bank BTPN Syariah based on DSN-MUI fatwa construction number: 04 / DSN-MUI / IV / 2000 dated April 1, 2000 concerning Murabahah in the first stipulation in paragraph 9 stated: "If the Bank wishes to represent customers to the customer for buying goods from third parties, the murabahah sale and purchase agreement must be made after the goods, in principle, become the property of the bank. The "sentence" in principle "in the DSN-MUI Fatwa is translated into practical terms by PT Bank BTPN Syariah with the following statement: "(in murabahah production equipment) if the Bank has confirmed the purchase of the purchase to the developer, then in principle the Bank has purchased the production equipment. Even though there is no cash flow to the developer in accounting, the Bank is committed to making payments for the purchase of production equipment to the developer represented by the customer. by using a wakalah agreement.